"Where do I find that?": creating a central shared documentation system for publishing staff using Google tools at the University of Michigan Library. Issue 10 (25th November 2014) - Norton, Alix
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This aim of this report is to summarize how Google Sites can be used as an open-source, intuitive, and robust solution for designing an intranet system for a unique library department. Michigan Publishing is a department within the University of Michigan (U-M) campus library system that also includes a revenue-based operation as the U-M Press. The need for a central documentation system has become apparent to organize and streamline policies and procedures in this unique library department. Google Sites was chosen as a solution to compile departmental documentation and serve as a collaborative space for the many units within Michigan Publishing. Design/methodology/approach – One librarian and one graduate student intern worked on this project for 5-10 hours a week over the course of three months. Michigan Publishing managers created an inventory showing all existing informational resources in the department, and were then interviewed about these resources. An initial "landing page" was created for this Google-based site, and more comprehensive content has since been migrated from existing informational resources to this central site. Findings – A specific Google Sites Staff Intranet for Michigan Publishing has been an integral solution for providing a one-stop, central area for current internal resources. It also fosters a sense of departmental identity and community, since there are many separate units within the department, each with a different focus and place within the larger library system. This site provides an online forum for collaboration, communication and policy codification. Originality/value – This report summarizes how Google Sites can be used as an open-source, intuitive, and robust solution for designing an intranet system for a unique library department.